PERANAN KUA DALAM MENANGANI PERKAWINAN DIBAWAH UMUR PASCA UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN - Syaufiq An Rahman Lubis (Kampus Akademik Publiser, 2024)
. This research aims to answer the questions stated in the problem formulation, which are: What roles does the Office of Religious Affairs (KUA) play in addressing the issue of underage marriage in Mojowarno sub-district? And how effective is the role of KUA in reducing the number of underage marriages in the sub-district?This research is qualitative and uses the empirical juridical approach with data collection through interviews, observations, and documentation.The results of the study conducted by the author reveal two main findings. Firstly, there are 34 cases of underage marriage recorded in 19 villages in Mojowarno sub-district. Among the perpetrators, 4 individuals did not complete primary school (SD), 10 individuals completed SD/MI, and 20 individuals completed junior high school (SMP/MTs). Secondly, the level of effectiveness of the KUA in Mojowarno sub-district in addressing underage marriage is still low.